In Vitro Assessment of Anthelmintic Activities of Rauwolfia vomitoria (Apocynaceae) Stem Bark and Roots against Parasitic Stages of Schistosoma mansoni and Cytotoxic Study - Emmanuel Mouafo Tekwu; Kwabena Mante Bosompem; William Kofi Anyan; Regina Appiah-Opong; Kofi Baffour-Awuah Owusu; Mabel Deladem Tettey; Felicia Amanfo Kissi; Alfred Ampomah Appiah; Veronique Penlap Beng; Alexander Kwadwo Nyarko (Journal of Parasitology Research)
Schistosomiasis is a Neglected Tropical Diseases which can be prevented with mass deworming chemotherapy. The reliance on a single drug, praziquantel, is a motivation for the search of novel antischistosomal compounds. This study investigated the anthelmintic activity of the stem bark and roots of Rauwolfia vomitoria against two life stages of Schistosoma mansoni. Both plant parts were found to be active against cercariae and adult worms. Within 2 h of exposure all cercariae were killed at a concentration range of 62.5–1000 µg/mL and 250–1000 µg/mL of R. vomitoria stem bark and roots, respectively. The LC50 values determined for the stem bark after 1 and 2 h of exposure were 207.4 and 61.18 µg/mL, respectively. All adult worms exposed to the concentrations range of 250–1000 µg/mL for both plant parts died within 120 h of incubation. The cytotoxic effects against HepG2 and Chang liver cell assessed using MTT assay method indicated that both plant extracts which were inhibitory to the proliferation of cell lines with IC50 > 20 μg/mL appear to be safe. This report provides the first evidence of in vitro schistosomicidal potency of R. vomitoria with the stem bark being moderately, but relatively, more active and selective against schistosome parasites. This suggests the presence of promising medicinal constituent(s).